PENGARUH GAYA HIDUP DIGITAL, SPONSORSHIP DAN INTENSITAS IKLAN TERHADAP PEMBELIAN ONLINE PADA MARKETPLACE SHOPEE (STUDY KASUS PADA GENERASI Z) - Zamroji Almursyid, M.; Irma Aprianti, Dian; Eica Gonadi, Jeannet (Jurnal GeoEkonomi, 2025)
This research is motivated by the increasingly rapid development of technology which will change people's digital lifestyles by using the internet to do everything more practically and quickly, one of which is using online shopping transactions in e-commerce. The aim of this research is to determine the impact of digital lifestyle, sponsorship and advertising intensity on online purchases on the Shopee marketplace (generation Z case study). The method used in this research uses a quantitative method with a purposive sampling technique, namely a sampling technique using exclusive considerations and a survey that is measured using a Likert scale, the data analysis technique used is multiple linear regression analysis and uses SPSS version 23 to determine the impact each variable. As a result of research, it is known that a digital lifestyle has a positive and significant effect on online purchases. Sponsorship has a positive and significant effect on online purchases. And for the simultaneous test, all variable X has an influence and is significant on variable Y